Defective mitochondrial rRNA methyltransferase MRM2 causes MELAS-like clinical syndrome. (25th August 2017) - Garone, Caterina; D'Souza, Aaron R; Dallabona, Cristina; Lodi, Tiziana; Rebelo-Guiomar, Pedro; Rorbach, Joanna; Donati, Maria Alice; Procopio, Elena; Montomoli, Martino; Guerrini, Renzo; Zeviani, Massimo; Calvo, Sarah E; et al.
Abstract: Defects in nuclear-encoded proteins of the mitochondrial translation machinery cause early-onset and tissue-specific deficiency of one or more OXPHOS complexes. Here, we report a 7-year-old Italian boy with childhood-onset rapidly progressive encephalomyopathy and stroke-like episodes. Multiple OXPHOS defects and decreased mtDNA copy number (40%) were detected in muscle homogenate. Clinical features combined with low level of plasma citrulline were highly suggestive of mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome, however, the common m.3243 A > G mutation was excluded. Targeted exome sequencing of genes encoding the mitochondrial proteome identified a damaging mutation, c.567 G > A, affecting a highly conserved amino acid residue (p.Gly189Arg) of the MRM2 protein. MRM2 has never before been linked to a human disease and encodes an enzyme responsible for 2'- O -methyl modification at position U1369 in the human mitochondrial 16S rRNA. We generated a knockout yeast model for the orthologous gene that showed a defect in respiration and the reduction of the 2'- O -methyl modification at the equivalent position (U2791) in the yeast mitochondrial 21S rRNA. Complementation with the mrm2 allele carrying the equivalent yeast mutation failed to rescue the respiratory phenotype, which was instead completely rescued by expressing the wild-type allele. Our findings establish that defective MRM2 causes a MELAS-like phenotype, and suggests the genetic screening of the MRM2 gene in patients with a m.3243 A > G negative MELAS-like presentation.